Salt stress in the psychrophilic diatom Fragilariopsis cylindrus - Krell, Andreas; Mock, Thomas; John, Uwe; Dieckmann, Gerhard; Valentin, Klaus-Ulrich (2006)
One of the most extreme environments in the polar regions is sea ice. Low temperatures, high salinities and high pH values together with extreme fluctuations in irradiance have lead to the development of a unique community in sea ice brine channels, which is dominated by diatoms. One of the best studied and most successful members of this community is the diatom Fragilariopsis cylindrus which is physiologically active at temperatures as low as 20°C and salinities of up to 100 PSU.To study molecular adaptations to this extreme habitat an expressed sequence tag (EST) approach was used, based on cultures subjected to elevated external salt concentrations (70 PSU). To 44 % of the sequences (1692 unigenes) a putative function could be assigned and a large number of genes involved in transport processes, oxidative stress defence, osmolyte synthesis and protein turnover as well as chaperones could be successfully identified, stressing the importance of these mechanisms in salt stress acclimatisation.Furthermore, four different full length sequences encoding a new class of ice-binding proteins yet unknown in animals and plants were found and further studies proved its occurrence in a number of polar diatom species, but not in mesophilic ones. These proteins are most probably exuded into the extracellular space and hence might be of fundamental importance in enabling survival in the brine channel system.The accumulation of the organic osmolyte proline synthesized upon osmotic stress was investigated. Measurements of transcript levels of four genes (P5CS, P5CR, OAT and ProDH) revealed an as yet unobserved regulation of the proline synthesis pathway in comparison to higher plants. A strong down regulation of P5CS and a simultaneously upregulated OAT suggested that ornithine rather than glutamate serves as a substrate for proline synthesis. The catabolic pathway via ProDH was also 3 fold up regulated after the salt shock indicating a high turnover of proline, but still enabling a net build up of proline 6 times higher than ...